COMFORT Behavior Scale instrument: validity and reliability test for critically-ill pediatric patients in Indonesia - Dina Nurpita Suprawoto; Nani Nurhaeni; Fajar Tri Waluyanti (MDPI AG, 2020)
The COMFORT Behavior Scale (CBS) is an instrument that has been validated in several languages to assess the levels of sedation in children. This project was implemented to identify the validity and reliability of CBS. The design used was an analytic descriptive cross-sectional approach. Fifty-one children aged 1 month to 18 years who received analgesic and/or sedation therapy were purposively selected and assessed for their sedation levels using CBS and the Nurse Interpretation of Sedation Score (NISS). The data were analyzed using the Mann-Whitney U test to measure the concurrent validity; each item was analyzed using Pearson correlation; inter-rater reliability was measured by the Kappa coefficient; and the internal consistency was measured by Cronbach's α. The results showed there was no significant correlation between the levels of sedation assessed using CBS and NISS (P= 0.118; α= 0.05). Six items in the CBS instrument were found to be valid (r= 0.348-0.813). The Cronbach's α for CBS was 0.873. Thus, the Indonesian version of CBS is valid and reliable in assessing sedation levels in children.